English Proficiency Test on Google Classroom During Pandemic Situation - Ervina CM Simatupang; Puspita Sari; Alvii Timothy Bungaran Siregar (Universitas Cokroaminoto Palopo, 2021)
This research is based on the results of Google Classroom implementation to both students and teachers at several high schools in Bandung in carrying out the English Proficiency Test. The test takers have regularly recognized and used Google Classroom as secondary application in online learning during the pandemic Covid-19. The research uses a qualitative and descriptive method. The objectives for the research are to describe the effectiveness of Google Classroom in conducting English Proficiency Test, to identify the materials feasibility when attached in Google Classroom, to obtain responses of test takers after conducting English Proficiency Test by Google Classroom. The research technique used is purposive sampling technique and virtual class observation, where the determination of participants research based on certain considerations. The results of this study indicate that the implementation of Google Classroom in English Proficiency Certification test during the current pandemic is relatively effective. Furthermore, the feasibility of materials posted or attached in the application help test takers to enhance their ability; and the responds taken from the test takers are positive. In other hand, based on the questionnaire shared to the test takers after the test, it shows positive sentiment regarding to the test organization, since it runs properly on their device.